Peptide Ligands that Interact with Newcastle Disease Virus: Selection, Characterization and Applications - Thurai Raja, Priadarishni Ramanujam (2003)
Newcastle disease, a highly contagious disease of the avian species is caused by the Newcastle disease virus (NOV). In Malaysia there have been 29 outbreaks of NOV reported this year alone. In spite of the availability of mass vaccination programmes, these sporadic outbreaks are believed to be the result of malpractice in backyard farming. The mechanism of NOV infection is still not clearly understood, making it difficult to validate any effective drug candidates. Bearing this in mind, a phage display random peptide library was used to identify peptide ligands that interact with NOV. A phage carrying the TLTTKLY sequence represented 97% of the total phage screened from the third round of biopanning against NOV strain AF2240. This phage was characterized and both cyclic and linear synthetic peptides bearing the homologous sequence were synthesized.